2010
DOI: 10.1007/s00792-010-0318-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biodiversity from Roopkund Glacier, Himalayan mountain ranges, India

Abstract: The bacterial diversity of two soil samples collected from the periphery of the Roopkund glacial lake and one soil sample from the surface of the Roopkund Glacier in the Himalayan ranges was determined by constructing three 16S rRNA gene clone libraries. The three clone libraries yielded a total of 798 clones belonging to 25 classes. Actinobacteria was the most predominant class (>10% of the clones) in the three libraries. In the library from the glacial soil, class Betaproteobacteria (24.2%) was the most pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 69 publications
5
29
2
Order By: Relevance
“…Earlier studies on Himalayas (Pradhan et al 2010;Shivaji et al 2011) reported Firmicutes as the abundant phylum contrary to the present study. Negligible reads detected in Arctic subsamples is in accordance with Chu et al (2010) who classified Firmicutes as the rarer phyla in Arctic soil.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Earlier studies on Himalayas (Pradhan et al 2010;Shivaji et al 2011) reported Firmicutes as the abundant phylum contrary to the present study. Negligible reads detected in Arctic subsamples is in accordance with Chu et al (2010) who classified Firmicutes as the rarer phyla in Arctic soil.…”
Section: Discussioncontrasting
confidence: 84%
“…This photosynthetic phylum is either reported to be present in low frequency or absent in the Himalayan regions (Pradhan et al 2010;Shivaji et al 2011;Stres et al 2014). Gemmatimonadetes and Verrucomicrobia found in the present study were reported from other cold habitats, though at a low frequency (Steven et al 2007;Wagner et al 2009;Pradhan et al 2010;Wu et al 2012). The core phyla obtained in the present study have also been reported from other cold habitats.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations